RESPONDING TO CREATIVE WRITING - HARPER, GRAEME (CAMBRIDGE SCHOLARS PUBLIS, 2020)
Creative writing is a responsive human activity. We use it to respond to the world, to our feelings, to ideas, to observations, to other people, to historical and cultural events, and to the wonders created in our imaginations. This book shows how we go about doing this responding. Contributors discuss practice-led research in creative writing. They look at the ways a writer can use language or employ genre and consider how we each define themes and subjects and use writing techniques to explore to these themes and subjects. In examining creative writing teaching, the contributions gathered he.